2020
DOI: 10.1002/cctc.202000140
|View full text |Cite
|
Sign up to set email alerts
|

A Janus‐type Heterogeneous Surfactant for Adipic Acid Synthesis

Abstract: A highly water‐dispersible heterogeneous Brønsted acid surfactant was prepared by synthesis of a bi‐functional anisotropic Janus‐type material. The catalyst comprises ionic functionalities on one side and propyl‐SO3H groups on the other. The novel material was investigated as a green substitute of a homogeneous acidic phase transfer catalyst (PTC). The activity of the catalyst was investigated for the aqueous‐phase oxidation of cyclohexene to adipic acid with 30 % hydrogen peroxide even in a decagram‐scale. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
0
13
0
2
Order By: Relevance
“…After crushing, nanosheets of catalyst 2 were formed (Figure 1b). To find evidence for a selective surface functionalization of catalyst 2, the material in the middle of crushing process was labelled with negatively charged citrate-capped Fe 3 O 4 nanoparticles (Fe 3 O 4 @citrate) according to our previously described procedure [30]. The loading of palladium in the catalyst was determined based on an atomic absorption spectroscopy (AAS) to be 0.22 mmol•g -1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After crushing, nanosheets of catalyst 2 were formed (Figure 1b). To find evidence for a selective surface functionalization of catalyst 2, the material in the middle of crushing process was labelled with negatively charged citrate-capped Fe 3 O 4 nanoparticles (Fe 3 O 4 @citrate) according to our previously described procedure [30]. The loading of palladium in the catalyst was determined based on an atomic absorption spectroscopy (AAS) to be 0.22 mmol•g -1 .…”
Section: Resultsmentioning
confidence: 99%
“…After crushing, nanosheets of catalyst 2 were formed (Figure 1b). To find evidence for a selective surface functionalization of catalyst 2, the material in the middle of crushing process was labelled with negatively charged citrate-capped Fe3O4 nanoparticles (Fe3O4@citrate) according to our previously described procedure [30]. After labelling the catalyst by mixing it with citrate@Fe3O4, the outer surface of the material that contains the nitrogen ligand can interact with the labelling agent (Figure 1c), while due to lack of noticeable functionality of the inner surface (i.e., relatively inert octyl groups), it remained almost remains untouched (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…n -Decane induces the formation of a hollow architecture and a particle size growth of up to 1 μm. To provide evidence for the selective surface bifunctionalization, catalyst 6 was treated with negatively charged, citrate-capped Fe 3 O 4 nanoparticles (citrate@Fe 3 O 4 ) according to the procedure of our recently published article …”
Section: Results and Discussionmentioning
confidence: 99%
“…It was shown that organic reactions can proceed efficiently inside temporarily formed microreactors. Besides, the Janus strategy was employed for the synthesis of a highly water-dispersible heterogeneous surfactant, allowing the aqueous-phase synthesis of industrially important dicarboxylic acids such as adipic acid and glutaric acid …”
Section: Introductionmentioning
confidence: 99%